2012
DOI: 10.1016/j.foodpol.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the consumer benefits of improving farm animal welfare to inform welfare labelling

Abstract: Policy makers in the European Union are envisioning the introduction of a community farm animal welfare label which would allow consumers to align their consumption habits with their farm animal welfare preferences. For welfare labelling to be viable the market for livestock products produced to higher welfare standards has to be sufficiently segmented with consumers having sufficiently distinct and behaviourally consistent preferences. The present study investigates consumers' preferences for meat produced to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 26 publications
5
61
0
2
Order By: Relevance
“…The findings are in line with Kehlbacher et al (2012): the higher the standards of animal welfare, the higher the WTP. Consequently, different WTPs can be achieved indicating that a multi-level labelling system is comprehensible.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The findings are in line with Kehlbacher et al (2012): the higher the standards of animal welfare, the higher the WTP. Consequently, different WTPs can be achieved indicating that a multi-level labelling system is comprehensible.…”
Section: Discussionsupporting
confidence: 83%
“…Another study conducted by Tonsor and Wolf (2011) showed that consumers are willing to pay a surplus of 20 % for pork and eggs labelled as produced without using gestation crates for sows or cages for laying hens. Kehlbacher et al (2012) provided further evidence that the WTP rises when the standards of the animal welfare improve. In their hypothetical study, the WTP is Moreover, in January 2013 two animal welfare labels with two levels each, "Für mehr Tierschutz" ("For more animal welfare") and "Tierschutz-Kontrolliert" ("Animal welfare controlled"), were introduced in Germany.…”
Section: Improving Animal Welfare By Multi-level Labellingmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering that food purchasing decision involves little information processing and minimal time expenditure (VANHONACKER and VERBEKE, 2014), clear and precise information is essential to consumer decision-making. In the specific case of WFP, label can take different formats to inform about animal rearing conditions (KEHLBACHER et al, 2012) and to allow consumers to understand the circumstances in which animals were reared, since the majority of consumer is distant from animal production systems. Again, availability seems to be a key-problem, in terms of quantity and quality of information offered to consumers.…”
Section: Labelingmentioning
confidence: 99%
“…The most prominent variations determinants are established to be socio-demographic factors. Previous research (Lagerkvist, Hess, 2011, Kehlbacher et al, 2012Grimsrud et al, 2013) consistently acknowledged that age, income, gender and the level of education played significant role in the distinguishment of consumers' willingness to pay for animal-friendly products. In addition, the presence of children in the household (Toma et al, 2012), as well as whether family owed a pet (Harper, Henson, 2001), influenced how prone they would be to pay premium price for products which considered animal welfare.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%